115k views
1 vote
Sin5A/SinA-cos5A/cosA=4cos2A​

User Logan H
by
5.0k points

1 Answer

3 votes

Answer:

See Explanation

Explanation:


( \sin5A)/(\sin A) - ( \cos5A)/(\cos A) = 4\cos2A \\ \\ LHS = ( \sin5A)/(\sin A) - ( \cos5A)/(\cos A) \\ \\ = ( \sin5A \:\cos A - \cos5A \: \sin A)/(\sin A \:\cos A ) \\ \\ = ( \sin(5A -A ))/(\sin A \:\cos A) \\ \\ = ( \sin 4A)/(\sin A \:\cos A) \\ \\ = ( 2\sin 2A \: \cos 2A)/(\sin A \:\cos A) \\ \\ = ( 2 * 2\sin A \: \cos A \: \cos 2A)/(\sin A \:\cos A) \\ \\ = ( 4\sin A \: \cos A \: \cos 2A)/(\sin A \:\cos A) \\ \\ =4\cos 2A \\ \\ = RHS \\ \\ thus \\ \\ ( \sin5A)/(\sin A) - ( \cos5A)/(\cos A) = 4\cos2A \\ \\ hence \: proved

User Katalonis
by
5.3k points